Abusado e Cidade de Deus: o limite textual entre o jornalismo e a literatura - Oliveira, Adriana Seibert de (2010)
Journalism and literature are two areas that have always been linked. When the first newspapers were published writers were responsible for their content. As a result, were present journalism elements in literary works. With this approach, and contamination of areas, a new genre has arisen: the literary journalism, which came up from journalism and uses the resources of literature to inform. Considering this contamination, this paper aims to show the mutual influences in each one of this areas. What is the literature contribution to journalism and what is the journalism influence in literature? These questions wil be answered by analyzing of the literary elements in the book-report Abusado, o dono do morro Dona Marta, written by Caco Barcellos, and the journalistic elements in the Paulo Lins novel Cidade de deus.